ANALISIS BUDAYA ORGANISASI,PENDIDIKAN DAN PELATIHAN,DAN MOTIVASI KERJA TERHADAP PENGEMBANGAN KARIR DI PT ARGA BANGUN BANGSA - RAHMI ULYA, (2022)
Analysis of Corporate Culture, Training, and Work Motivation On Career Development at PT Arga Bangun Bangsa By Rahmi Ulya ABSTRACT The research is quantitative research aimed at analyzing the influence of cultural, training, work motivation of career development and work motivation are intervening variable. The population of the research is employees in PT Arga Bangun Bangsa with samples 126 respondents. Data was collect through a questionnaire. The analysis used is technical analysis method PLS ( Partial Least Square).This research result indicates that the culture of the organization will not affect career development and cultural organization also will not affect pengembagan career through. motivation In contrast to the education and training of the research explained that education and training affect career development and variable education and training also influences the career development through Keywords: Culture Organization, Training, Work Motivation, Career Development